Carbon Nanofibers Encapsulated Nickel‐Molybdenum Nanoparticles as Hydrogen Evolution Catalysts for Aqueous Zn−CO2 System. Issue 6 (20th April 2020) - Asokan, Arunchander; Lim, Chaehyun; Kim, Jeongwon; Kwon, Ohhun; Lee, Hansol; Joo, Sangwook; Jeong, Hu Young; Kim, Guntae
Abstract: Carbon capture, utilization and storage techniques have been studied extensively to reduce atmospheric carbon dioxide. However, CO2 conversion technologies are not widely proposed due to sluggish conversion rate, high energy consumption and need for precious metals as catalysts. Therefore, novel metal‐CO2 electrochemical cell has been proposed to utilize CO2 to produce electricity and H2 gas continuously. Electrochemical hydrogen evolution reaction under neutral condition has demanded the overall device performance. Herein, we have developed non‐precious NiMo‐carbon nanofiber‐based catalyst with unique matchstick‐like morphology using low temperature CVD technique and demonstrated in aqueous Zn−CO2 system. The NiMo alloy offers excellent activity by promoting hydrogen adsorption/desorption and chemically bonded carbon nanofiber assists catalytic activity by providing charge transfer. Due to superior characteristics, NiMo‐carbon nanofiber exhibits significant HER activity (over‐potential of 268 mV at 10 mA cm ‐2 ) in CO2 ‐saturated 1 M KOH and superior cell performance in aqueous Zn−CO2 system (peak power density of 25 mW cm −2 ). In addition, the stability of the catalysts has also been investigated using chronopotentiometry and the results have compared with commercial Pt/C catalysts. We are hopeful that the present study will provide insights into developing non‐precious electrocatalysts, particularly for metal‐CO2 electrochemical conversion devices. Abstract : NiMo/CNF for Aqueous Zn−CO2 system : The unique matchstick‐like morphology of NiMo/CNF catalyst provides an outstanding catalytic HER activity and structural durability compared to the commercial Pt/C. With this, we are hopeful that the NiMo‐based electrocatalyst described in the present investigation offers a new avenue for the design and development of novel and highly active HER catalysts for the combined eco‐friendly hydrogen gas production as well as electrochemical conversion devices.